Implementasi Untuk Meningkatkan Kinerja UMKM Terhadap Kemampuan Menghadapi Daya Saing Pada Sektor Kuliner di Kecamatan Karang Bahagia - Ella Apriyanti; Sisca Risnawati Apriani; Ana Fitria; Ifah chofifah; Devina Syafa Nabila (Jurnal Ekonomi Syariah Pelita Bangsa, 2025)
This study aims to examine the impact of quality management implementation on improving the performance of Micro, Small, and Medium Enterprises (MSMEs) in the culinary sector in Karang Bahagia District. Using a quantitative method based on questionnaires, data were collected from 88 MSME operators to analyze the level of quality management principles implementation, the factors influencing it, and its impact on business performance. The findings reveal that most MSME operators have implemented basic quality management elements such as Standard Operating Procedures (SOPs) and quality control, although aspects such as internal audits and performance measurement remain limited. Factors such as knowledge, training, owner involvement, and capital constraints were identified as key determinants of successful quality management implementation. MSMEs that adopted quality management practices demonstrated significant improvements in product quality, operational efficiency, sales, and customer loyalty. This study provides both theoretical and practical contributions to the development of more effective quality management strategies in the MSME sector.